2009
DOI: 10.1007/s10722-009-9432-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of Hungarian and Turkish watermelon (Citrullus lanatus (Thunb.) Matsum. et Nakai) genetic resources

Abstract: Thirty-nine Hungarian accessions either collected from different regions of Hungary or obtained from gene banks and 11 Turkish accessions representing particular regions of Turkey were evaluated and compared for morphological characteristics. Qualitative characters were obtained according to the modified UPOV descriptor list for 58 characters. Sixteen quantitative characters (hypocotyl length, cotyledon width and length, length of main stem, number of nodes, length and width of leaf, length of petiole, length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…(Velayudhan et al, 1999;Sasikumar, 2005;Hussain et al, 2008;Keeratinijakal et al, 2010), Alpinia spp. (Ravindran et al, 1994;Kladmook et al, 2010), as well as other crop species such as kale (Cartea et al, 2002), Vitis vinifera (Ortiz et al, 2004), greater yam (Hasan et al, 2008), watermelon (Szamosi et al, 2009), melon (Oumouloud et al, 2009), wheat (Dos Santos et al, 2009) and cowpea (Ghalmi et al, 2010). (Ravindran et al, 1994;Kladmook et al, 2010), as well as other crop species such as kale (Cartea et al, 2002), Vitis vinifera (Ortiz et al, 2004), greater yam (Hasan et al, 2008), watermelon (Szamosi et al, 2009), melon (Oumouloud et al, 2009), wheat (Dos Santos et al, 2009) and cowpea (Ghalmi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(Velayudhan et al, 1999;Sasikumar, 2005;Hussain et al, 2008;Keeratinijakal et al, 2010), Alpinia spp. (Ravindran et al, 1994;Kladmook et al, 2010), as well as other crop species such as kale (Cartea et al, 2002), Vitis vinifera (Ortiz et al, 2004), greater yam (Hasan et al, 2008), watermelon (Szamosi et al, 2009), melon (Oumouloud et al, 2009), wheat (Dos Santos et al, 2009) and cowpea (Ghalmi et al, 2010). (Ravindran et al, 1994;Kladmook et al, 2010), as well as other crop species such as kale (Cartea et al, 2002), Vitis vinifera (Ortiz et al, 2004), greater yam (Hasan et al, 2008), watermelon (Szamosi et al, 2009), melon (Oumouloud et al, 2009), wheat (Dos Santos et al, 2009) and cowpea (Ghalmi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological characters, together with physiological, phenological and agronomic descriptors, are the starting point of the characterisation work (Ayres Carvalho & Quesenberry, 2009; Diederichsen, 2009; Gonçalves et al , 2009; Hend et al , 2009; Karimi et al , 2009; Nieto‐Ángel et al , 2009; Szamosi et al , 2009; Vieira et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and genetic characterization of Hungarian and Turkish accessions of watermelon (including C. lanatus and C. colocynthis) revealed that germplasm resources present a wide range of diversity (Sari et al, 2005;Solmaz and Sari, 2009;Solmaz et al, 2010). However, accessions of the two countries show many similarities and therefore cannot be separated clearly (Szamosi et al, 2009). In the present study, comparison of the four groups using a MANOVA combined with factorial discriminant analysis, allowed the classification of accessions according to agromorphological characters.…”
Section: Eigenvectormentioning
confidence: 83%